PENGARUH TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP EFEKTIVITAS KOMUNIKASI ANTARPRIBADI MAHASISWA - Syahruddin Syahruddin (KAREBA : Jurnal Ilmu Komunikasi, 2020)
The high level of human interaction with the screen or screen technology (cellphone, computer) as part of the information needs raises a human behavior that is more concerned with face to screen relationship than face to face. The purpose of this study was to determine the effect of Information and Communication Technology on the effectiveness of interpersonal communication of students in Kendari City and what impacts resulted from the development of information and communication technology. The research location is a university in the Kendari City area. Data collection is done using the questionnaire (questionnaire), interviews and documentation. Respondents numbered 75 people, while the research informants totaling seven people were determined purposively. The results of the study show that the variable X (information and communication technology) influences the Y variable (effectiveness of interpersonal communication) of students in Kendari city where the variables together have an effect of 0.596 located between the values 0.50-0.69 indicating that the correlation coefficient value in a strong relationship.